Conversion of Green Coconut Shell and Husk into Biobriquette Using Jatropha seed Adhesive - Utami, Putri Agus; Sudarmi, Raudhatul Aulianatia; Sahara, Siti; Anwar, Khairul; Mahidin, Mahidin; Djuned, Fauzi Muhammad (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Green coconut shell and husk (GCSH) waste had the potential to pollute the environment if not properly utilized. As a solution, innovations in processing GCSH into biobriquettes could generate eco-friendly renewable energy with economic value. This study aimed to optimize the utilization of GCSH as a raw material for biobriquettes by adding jatropha seeds as an adhesive, as well as evaluating the characteristics of the produced biobriquettes. Fabrication of biobriquette was carried out using two methods: conventionally (without burning) and by pyrolysis (with burning) at temperatures of 380C, 430C, and 480C for 3.5 hours. The charcoal obtained from pyrolysis was mixed with jatropha seed adhesive at concentrations of 15%, 20%, and 25%, then molded at a pressure of 110 kg/cm and dried at 105C. The results showed that pyrolysis temperature and adhesive concentration affected the moisture content, ash content, calorific value, compressive strength, and combustion rate of the biobriquettes. Optimum conditions were achieved at a pyrolysis temperature of 430C with the addition of 25% adhesive, resulting in biobriquettes with high calorific value (6367.74 cal/g), low moisture content (7.44%), and good combustion rate (0.10219 g/min). This study proved that utilizing GCSH waste and jatropha seeds for biobriquettes had great potential as an efficient and sustainable source of renewable energy.